440 10 kHz Spinal Cord Stimulation (SCS) Provides Significant, Durable Pain Relief for Patients with Painful Diabetic Neuropathy (PDN): 24-Month Results. (April 2023) - Petersen, Erika A.; Stauss, Thomas; Scowcroft, James; Jaasma, Michael; White, Judith; Sills, Shawn; Amirdelfan, Kasra; Guirguis, Maged; Xu, Jijun; Yu, Cong; Nairizi, Ali; Patterson, Denis; et al.
Abstract : INTRODUCTION: Approximately 37 million Americans have diabetes, 1 with 25-30% experiencing PDN. 2 High-frequency (10 kHz) SCS has been shown to provide substantial symptom relief for PDN, 3 and here we report durability of these outcomes to 24 months (24M). METHODS: This prospective, multicenter, RCT evaluated 10 kHz SCS with these key inclusion criteria: PDN symptoms ≥12 M refractory to medications, lower limb pain intensity ≥5 cm (0-10 cm visual analog scale [VAS]), and hemoglobin A1c ≤ 10%. Patients (n = 216) were randomized 1:1 to 10 kHz SCS plus CMM or CMM alone, with optional crossover at 6M. RESULTS: At 6M, patients receiving 10 kHz SCS experienced average pain relief of 76.1% (95% CI: 70.5–81.6%), which increased to 82.0% (95% CI: 77.3–86.6%) at 24M. At 24M, 10 kHz SCS patients experienced 70% decreases in pain-associated sleep disturbance and interference with mood and daily activities. At 24M, neurological improvements were observed in 72% of patients receiving 10 kHz SCS. After 6M, 93% of eligible CMM patients elected to cross over to 10 kHz SCS, while zero 10 kHz patients crossed over. With 10 kHz SCS, both groups experienced similar, significant reductions in pain and pain-associated interference. There were zero device explants due to lack of efficacy and eight (5.2%) procedure-related infections (n = 3 resolved with antibiotics; n=5 explanted), which is within the range reported for SCS in non-diabetic patients (2.5-10%).4 CONCLUSIONS: This is the largest RCT to date for SCS management of PDN. The 24M results support that 10 kHz SCS can provide safe, durable pain and symptom relief for PDN. REFERENCES: 1 CDC. National Diabetes Statistics Report; 2022. 2 Finnerup et al. Lancet Neurol 2015; 14(2):162-73. 3 Petersen et al. Diabetes Care; 45(1):e3-e6. 4 Eldabe et al. Pain Med 2016; 17(2):325-36.